Clínica Médica e Cirúrgica de Pequenos Animais. - Sousa, Antônio Gomes Costa Neto de (Universidade Federal do Tocantins, 2023)
The purpose of this study was to describe the routine and main activities performed at Hospital Veterinário São Francisco de Assis, describing the follow-up of the technical activities performed at the Hospital and reporting the clinical and surgical casuistry of the internment sector and a clinical case report followed during the Internship. Data were collected based on participant observation, from December 2016 to February 2017. A total of 226 dogs and cats were interned. The females represented the highest number of internment for dogs (53.5%), while for cats, the highest number of males (57.1%). The reproductive diseases were the most prevalent for both species with 28.8 and 33.8%, respectively. Was accompanied a case of a dog with coinfection by Ehrlichia sp. and Anaplasma sp. Which presented apathy, inappetence, hemorrhage, pale mucous membranes, hyperthermia and the presence of ticks. The laboratory findings were normocytic normochromic anemia, pancytopenia, and hypergammaglobulinemia. The animal responded well to the treatment imposed, with progressive improvement of the clinical condition. The development of practical skills is essential for student training. The canine species was more prevalent in the hospitalization sector and the reproductive affections were more frequent. In the case study, the diagnosis of co-infection by Ehrlichia sp. And Anaplasma spp. With medullary aplasia. The Supervised Curricular Internship allowed to build a bridge between the knowledge acquired in the classroom and the practice, allowing the improvement and obtaining more skill in the execution of veterinary medical procedures.